NILAI-NILAI EKONOMI ISLAM DALAM TRADISI MALAN MASYARAKAT DAYAK BAKUMPAI - Misra, Isra; Sadikin, Ali (Jurnal Studi Agama dan Masyarakat, 2021)
The Malan tradition or farming of Bakumpai Dayak society is a hereditary tradition handed down by ancestors. Malan is a social activity in agriculture, especially in farming, starting from clearing fields, cutting down forests, burning fields, planting rice and harvesting rice. This study was a field research with a qualitative approach in the form of phenomenology and contextual Islamic economics. The informants were people who farmed around Murung Raya Regency. Sources of data were primary data and secondary data. Primary data were data from observations and interviews. While secondary data were data in the form of documentation. The results showed that in Malan tradition of Bakumpai Dayak society, Islamic economic values were found in the form of togetherness and balance, help each other, cooperation, sharing and kindship. Malan activities were activities that form the basis of society in fulfilling basic needs (rice). The inhibiting factor for Malan's current activities was the government regulation that strictly prohibits burning forests and land. Malan activity was an activity that really helped rural communities in fulfilling their foods. The economic contribution to the Malan Tradition was enormous for society.